An optimized elliptic curve digital signature strategy for resource-constrained devices - Nawras H. Sabbry; Alla Levina (Scientific Reports)
Abstract Ensuring robust security in resource-constrained environments, such as microcontrollers used in Unmanned Vehicle systems (UVS), poses significant challenges due to the computational and memory demands of cryptographic algorithms. This research addresses these challenges by proposing an optimized ECC digital signature method designed for such environments. The method incorporates two key enhancements: optimizing scalar point multiplication using the cyclic group property of elliptic curve points and the additive inverse property in group theory, and secondly, adopting a deterministic private nonce generation approach, while excluding the public nonce ( $$R$$ ) from the calculation of the challenge to improve signing efficiency. The proposed method was implemented on an Arduino Atmega 2560 microcontroller, a representative resource-constrained platform, using low-level programming techniques. The results demonstrate significant improvements in computational efficiency and memory usage across all steps of the digital signature process (key generation, signing, and verification), while maintaining robust security standards. This work underscores the feasibility of deploying secure and efficient ECC-based digital signatures in constrained environments.